Extraction and Characterization of gelatin from goat skin - Reddy, P Sowmya; Priya, K B; Belore, Balaji M; Mishra, Bidyut Prava; Banerjee, Rituparna; Gangaraju, G; Indumathi, J; Reddy, G V Bhaskar; Maheswarappa, Naveena B; Judy, L (Journal of Meat Science, 2024)
The present study was conducted to optimize the pretreatment and extraction protocols for gelatin from goat skin. The physico-chemical properties of gelatin extracted from goat skin under different pretreatment conditions viz., scalding (65℃ for 5 min), 0.1 M NaOH for 2 h, 0.25 M NaOH for 2h and extraction temperatures (60℃ and 65℃) were studied. Pretreatment with 0.1 M NaOH and extraction at 65℃ (6 h) recorded the highest yield (8.42±0.02%) as well as better gel clarity (53.03±0.18%) and instrumental colour values. The scanning electron microstructure of goat skin gelatin displayed a compact network of protein strands without any void spaces. The gel strength and viscosity of goat skin gelatin were 437.56 g bloom and 15.73 cP respectively. The SDS-PAGE fractionation of gelatin proteins showed the presence of distinct α, β and γ-chains. These findings suggest that goat skin has an immense potential to be employed for gelatin extraction and can be used as an alternative to gelatin from other sources.